2018
DOI: 10.1007/s11695-018-3378-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Pre-operation Social Connectedness Associated with Weight Loss up to 2 Years Post Bariatric Surgery?

Abstract: Supportive relationships are important contributors to weight loss from bariatric surgery. If replicated in future studies, these findings could inform clinical care and interventions aimed at improving support systems of bariatric surgery candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
6
1
2
Order By: Relevance
“…Further, many patients do not regularly attend MBS support groups suggesting that they seek and rely on other sources of social support (e.g., family and friends). 5 Research that has directly assessed PSS in MBS patients suggests that higher PSS levels are associated with a wide range of benefits including fewer surgical complications, greater weight loss, lower depression and disordered eating, and positive changes in PA. 5,[10][11][12][13] Conversely, both quantitative and qualitative data suggest that deficits in PSS contribute to smaller weight losses, reduced surgery satisfaction and feelings of loneliness, struggle, and self-blame during weight recurrence. 14,15 Despite growing evidence that higher PSS levels are associated with improved behavioral adherence, psychological health, and weight outcomes after MBS, the design and methodological limita- measured via accelerometry) and eating regulation (dietary restraint and disinhibition measured via EMA) behaviors on that day.…”
Section: Introductionmentioning
confidence: 99%
“…Further, many patients do not regularly attend MBS support groups suggesting that they seek and rely on other sources of social support (e.g., family and friends). 5 Research that has directly assessed PSS in MBS patients suggests that higher PSS levels are associated with a wide range of benefits including fewer surgical complications, greater weight loss, lower depression and disordered eating, and positive changes in PA. 5,[10][11][12][13] Conversely, both quantitative and qualitative data suggest that deficits in PSS contribute to smaller weight losses, reduced surgery satisfaction and feelings of loneliness, struggle, and self-blame during weight recurrence. 14,15 Despite growing evidence that higher PSS levels are associated with improved behavioral adherence, psychological health, and weight outcomes after MBS, the design and methodological limita- measured via accelerometry) and eating regulation (dietary restraint and disinhibition measured via EMA) behaviors on that day.…”
Section: Introductionmentioning
confidence: 99%
“…Embora ainda não esteja claro como ocorre essa influência, estudos sugerem que incluir o apoio social no pós-operatório poderia promover melhores desfechos no tratamento, uma vez que o apoio familiar pode auxiliar na adesão às mudanças no estilo de vida necessárias para a manutenção dos resultados alcançados com a cirurgia bariátrica. Por outro lado, a ausência do apoio social poderia dificultar a realização dessas mudanças, bem como impactar de forma negativa os resultados pós-cirúrgicos de perda de peso e melhora da saúde (Lent et al, 2016;Sharman et al, 2017;Tymoszuk et al, 2018).…”
Section: Introductionunclassified
“…Various studies have demonstrated the importance of social support in different phases of obesity [ 27 ]. Social support is associated with making the decision to undergo bariatric surgery [ 28 ], post-surgery results [ 29 , 30 , 31 , 32 ], stress levels [ 33 ], information prior to treatment [ 34 ] and coping strategies [ 35 ]. Other studies have explored the experiences of patients in MO support groups after undergoing bariatric surgery [ 36 , 37 ] or patients who are expecting bariatric surgery alongside their partners [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%